1984
DOI: 10.1111/j.1469-8749.1984.tb04409.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding and Child Development at Five Years

Abstract: 19836) 'Breast feeding, eczema, asthma and hay fever.' Journal of Epidemiology and Community Health, 37, 95-99. 265-268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
3

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 24 publications
1
25
0
3
Order By: Relevance
“…Human breast milk may support neurological development by providing long-chain polyunsaturated fatty acids [11]. This effect seems to be robust to adjustment for confounders [2,5,12] and is detected from early childhood [13,14] to young [12] and late [15] adulthood and even among older persons [16]. However, other observational studies [17][18][19][20] and one randomized controlled trial in preterm infants [21] have not detected any association although in the trial, after taking the lower nutritional value of donor breast milk into consideration, Lucas et al concluded that ''our data add significant support to the view that breast milk promotes neurodevelopment'' [21].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Human breast milk may support neurological development by providing long-chain polyunsaturated fatty acids [11]. This effect seems to be robust to adjustment for confounders [2,5,12] and is detected from early childhood [13,14] to young [12] and late [15] adulthood and even among older persons [16]. However, other observational studies [17][18][19][20] and one randomized controlled trial in preterm infants [21] have not detected any association although in the trial, after taking the lower nutritional value of donor breast milk into consideration, Lucas et al concluded that ''our data add significant support to the view that breast milk promotes neurodevelopment'' [21].…”
Section: Introductionmentioning
confidence: 89%
“…Some evidence gathered from many observational studies [1][2][3][4][5][6][7][8][9][10] and one meta-analysis [11] undertaken over the last three decades indicates that breast feeding has a small but statistically significant positive effect on cognitive function. Human breast milk may support neurological development by providing long-chain polyunsaturated fatty acids [11].…”
Section: Introductionmentioning
confidence: 97%
“…A growing literature suggests that a relationship between breastfeeding and cognitive development exists (Silva, Buckfield et al 1978;Clandinin, Chappell et al 1980;Fergusson, Beautrais et al 1982;Taylor and Wadsworth 1984;Doyle, Rickards et al 1992;Wharton 1992;Makrides, Neumann et al 1994;Michaelson, Larsen et al 1994;Malloy and Berendes 1998;Quinn, O'Callaghan et al 2001;Oddy, Kendall et al 2003). In a recent critical evaluation (Drane and Logemann 2000) of the three methodological standards described by Bauchner (Bauchner, Leventhal et al 1986), definition of outcome, correct classification of infant feeding type and control of potential confounding variables were determined in relation to cognitive development.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In a recent critical evaluation (Drane and Logemann 2000) of the three methodological standards described by Bauchner (Bauchner, Leventhal et al 1986), definition of outcome, correct classification of infant feeding type and control of potential confounding variables were determined in relation to cognitive development. The evaluation found that adherence to an infant feeding standard was poor with most studies classifying partial and exclusive breastfeeding together and only five considering feeding as a continuous variable (Taylor and Wadsworth 1984;Morrow-Tlucak, Haude et al 1988;Bauer, Ewald et al 1991;Lucas, Morley et al 1992;Horwood and Fergusson 1998). Most studies adjusted for confounding factors including maternal education, socioeconomic status, birthweight and birth order.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Breastfeeding may also affect secretion of hormones, such as oxytocin, that enhance positive affect in both the mother and the child [9][10][11] . The few previous studies on the effects of breastfeeding on a child's later personality suggest that breastfeeding may foster mental health [12][13][14][15][16][17] , but firm population-based longitudinal evidence is lacking.Hostility is a personality construct that represents the opposite of warm attachment and that is closely related to a wide range of social and health problems [18][19][20][21] , including mental health outcomes. Although the importance of cold and unsupportive parenting for the development of hostility has been recognized [22] , we are aware of no study focusing on the significance of breastfeeding on offspring hostility.…”
mentioning
confidence: 99%